Neuro-olfactory dynamics: electroencephalographic insights into dysfunction - Francisco Alves de Sousa; Sara Costa; João Tavares Correia; Sara Azevedo; Ana Nóbrega Pinto; Mariline Santos; Luís Meireles (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Olfaction is linked to cognition. Understanding brain activity during olfactory dysfunction (OD) could improve knowledge about olfaction itself and associated treatments like olfactory training (OT).